Quatre Etoiles / Muhammad Hafis Kamaruddin ... [et al.] - Kamaruddin, Muhammad Hafis; Abg Raduan, Abg Alif; Ahmad Tarmidi, Ahmad Qusyairi Amin; Azahari, Muhammad Bismi Haziq (2019)
Cooking is an art which several ingredients are put together to food, meal and also drinks. The act of cooking were dated long ago where the exact date long ago where the exact date are unknown but it start about 1.5 million years ago. Cooking were invented to handle several problem such as kill microorganism in food and make it easy to chew. There are a lot of ways we can cook our food. Some of the basic ways are boiling, heating, grilling, frying and smoking. There's also more specific way of cooking such as indirect smoking, deep frying, poaching and sauté. Through this various ways of cooking, a lot of cooking style were invented as the time goes on. Most of the time, the cooking style of place were affected by the region of the country. For example, the eastern cooking style and Asian cuisine cooking style. Our business are solely aiming for the western cooking style. We are starting a class about cooking, and we are focusing on teaching western style cooking using domestic ingredients as replacement of ingredients that are not available locally. There's a bunch of brunch on western cooking style, such as American style, French style and British style. These classes cover all of western style cooking brunch. A lot of new recipe will be introduce to our students weekly. The aim of this class is to introduce unique cultures and ways of cooking is Asian cooking style. In Asian cooking style, a lot of poaching and food. However, by introducing western cooking style, we can cut or reduce the spicy and oil in Malaysian food without sacrificing the taste of food. This is because western style cooking tend to smoke and grill their food. By teaching the western style cooking, we can promote a healthier lifestyle. In this business, we are targeting on housewife as main target. Housewives needs to take care of their family. So, they need to cook a healthy meal for the whole family. Moreover, housewives were always looking for a new recipe to try which we provide in our class. We also targeting culinary student that want to learn new things such handling kitchen appliances and creating new recipe. Not only that, owner of cooking business was also our target. Some want them mat want to add new recipe to their menu.